TANGGUNG JAWAB PELAKU USAHA TERHADAP KERUSAKAN BARANG KREDIT BERGARANSI (KOMPILASI HUKUM EKONOMI SYARIAH) - Tussyadiyah, Halimah; Zahara, Fatimah (Legal Standing : Jurnal Ilmu Hukum, 2024)
Manufacturers of electronic products often provide warranties to customers, subject to certain conditions, because of the inherent risk of future defects or loss in any transaction involving such items. However, there are times when the collateral for installments is damaged or even lost. This research aims to determine the views of the Compilation of Sharia Economic Law regarding the responsibility of business actors for damage to collateralized credit goods. In this research, the method used is empirical juridical. Data collection uses interviews and data analysis techniques using legal content analysis and case studies. The research results show that the Compilation of Sharia Economic Law states that business actors must provide compensation to customers for damaged goods, and the furniture shop's policy in paying to repair or replace damaged goods is in accordance with this obligation, because it is in line with Islamic principles.